Autotrophic antimonate bio-reduction using hydrogen as the electron donor. (1st January 2016) - Lai, Chun-Yu; Wen, Li-Lian; Zhang, Yin; Luo, Shan-Shan; Wang, Qing-Ying; Luo, Yi-Hao; Chen, Ran; Yang, Xiaoe; Rittmann, Bruce E.; Zhao, He-Ping
Abstract: Antimony (Sb), a toxic metalloid, is soluble as antimonate (Sb(V)). While bio-reduction of Sb(V) is an effective Sb-removal approach, its bio-reduction has been coupled to oxidation of only organic electron donors. In this study, we demonstrate, for the first time, the feasibility of autotrophic microbial Sb(V) reduction using hydrogen gas (H2 ) as the electron donor without extra organic carbon source. SEM and EDS analysis confirmed the production of the mineral precipitate Sb2 O3 . When H2 was utilized as the electron donor, the consortium was able to fully reduce 650 μM of Sb(V) to Sb(III) in 10 days, a rate comparable to the culture using lactate as the electron donor. The H2 -fed culture directed a much larger fraction of it donor electrons to Sb(V) reduction than did the lactate-fed culture. While 98% of the electrons from H2 were used to reduce Sb(V) by the H2 -fed culture, only 12% of the electrons from lactate was used to reduce Sb(V) by the lactate-fed culture. The rest of the electrons from lactate went to acetate and propionate through fermentation, to methane through methanogenesis, and to biomass synthesis. High-throughput sequencing confirmed that the microbial community for the lactate-fed culture was much more diverse than that for the H2 -fed culture, which was dominated by a short rod-shaped phylotype of Rhizobium ( α-Protobacteria ) that may have been active in Sb(V) reduction. Graphical abstract: Highlights: H2 was able to drive the autotrophic bioreduction of Sb(V) as electron donor. H2 had higher electron utilization efficiency in reducing Sb(V) than lactate. Lactate-fed culture was much more diverse than that for the H2 -fed culture. The H2 -fed culture was dominated by a short rod-shaped phylotype of Rhizobium.